One Brand, Many Trajectories: Narrative Navigation in Transmedia - Feiereisen, Stephanie; Rasolofoarison, Dina; Russell, Cristel Antonia; Schau, Hope Jensen (Journal of Consumer Research, 2021)
AbstractIn an era of unprecedented consumer access to media and the tools to control narrative delivery, speed, and exposure to transmedia content, there is no longer the illusion of a cohesive narrative managed by a recognized singular author or unified authorial voice. Instead, consumers carve their own trajectories through brand narratives. Our multimethod inquiry of television series viewing, based on a combination of interviews, diaries, video recordings followed by member-check interviews and online forum analyses, identifies two key forces that guide narrative navigation: how consumers manage a text’s gravitational pull and its permeability to transmedia content. We find that consumers shape their own trajectories by adopting and/or moving between nine documented narrative positions. This more nuanced understanding of narrative consumption in a transmedia environment offers new insights for the study of narrative brand spaces and brand storytelling.